A computer aided learning package about countries (CALPAC) / Lim Kheng Teong - Lim, Kheng Teong (2003)
A computer learning package about countries (CALPAC) is developed with its goal to provide an alternative way for the users to learn information about some countries in the world by using computer technology. CALPAC is designed to be easy to use, yet provide the useful functionality needed to learn efficiently. The information provided by the system should be from the authoritative sources to make the information is more reliable. Functions that are provided are countries information learning, database maintenance, indexing and game. The game provided in the CALPAC hopes can even make the learning process more efficient and effective. The database of the CALPAC is a multimedia database which contains electronic text, images, audio and video. The limitation is the CALPAC only covers 30 countries from 5 different continents in the world. CALPAS is developed under Microsoft Visual Basic .NET and with the support by Macromedia Flash MX. Apart from that, Microsoft Access is used as the database management system. Under the combination of these tools, the project should produce a very high impact application. Since the local market still lack of this type of learning package, it is possible that this package is needed very much. It is believed that the CALPAC will beneficial to the people who are interested in this field.